Compression tests of C-FRCM jacket confined hollow section RC columns. (June 2021) - Zhu, Ji-Hua; Chen, Ju; Feng, Yuan; Liu, Cheng-Bin
Abstract: This paper describes an experimental investigation on column tests of carbon fiber-reinforced cementitious matrix (C-FRCM) jacket confined hollow section reinforced concrete (RC) columns. The experimental program consists of twenty columns on two series of confined specimens and two series of unconfined specimens. Test specimens comprise of columns having solid section and hollow section with different hollow ratios. The material properties of C-FRCM were measured through tensile coupon tests. The load carrying capacities, load-end shortening responses, load–strain curves and failure modes of RC column specimens are presented and discussed in this paper. It is shown that the hoop strain of columns under compression decreases with the increase of the hollow ratio, which means the reduction of confinement effect. The effect of hollow ratio on the compressive strength of confined concrete was discussed and an equation was proposed. It is shown that the predictions from the proposed equation agree with the test results generally well.